2021
DOI: 10.1371/journal.pone.0256360
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of groundwater and source identification in a coastal city

Abstract: A coastal city is studied in this paper. Based on 42 groundwater sampling points, a Piper diagram, the Shukarev classification, the Pearson correlation analysis, Gibbs plots and the ion proportional coefficient method are used to analyze the chemical characteristics and material source. The results show that the groundwater quality in the study area varies greatly from north to south. In the northern inland area (AREA I), the main anions and cations are H C O 3 - and Ca2+, and the hydrochemical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…This method has been used for the evaluation of groundwater quality. Strong correlations between major ions are also reported by Miao et al [40]. This situation evidenced that the groundwater quality of a coastal city in China was affected by various factors, such as dissolution and water evaporation.…”
Section: Multivariate Statistical Analysissupporting
confidence: 62%
“…This method has been used for the evaluation of groundwater quality. Strong correlations between major ions are also reported by Miao et al [40]. This situation evidenced that the groundwater quality of a coastal city in China was affected by various factors, such as dissolution and water evaporation.…”
Section: Multivariate Statistical Analysissupporting
confidence: 62%
“…Classifying hydrochemical types can provide a more intuitive analysis of the chemical characteristics of water bodies in different basins. By using the Piper ternary diagram and the Shukarev classification method [36], comparisons of the main ion concentrations in the five watersheds were conducted, leading to the categorization of hydrochemical types (Figure 5 and Table 1). It can be observed that the proportions of each ion's concentration in river water and groundwater are similar, while the concentration of Cl − is higher in lake water.…”
Section: Differences In Hydrochemical Types and Their Causesmentioning
confidence: 99%
“…The absence of lake water samples in the Gibbs diagram of the Golmud River is due to a TDS that exceeds 10 5 mg/L, indicating that the lake water is influenced by other factors. In the case of the Bayin River, one water sample in the summer groundwater falls outside the graph in the Cl − /(Cl − + HCO3 − ) ratio diagram, suggesting that hydrochemical characteristics may be influenced by other factors, such as human activities [36].…”
Section: Differences In Hydrochemical Types and Their Causesmentioning
confidence: 99%
“…The coastal regions adjoining seawater environments typically featured the presence of Cl − −Na + ions. 26 Given these circumstances, PFOA, in conjunction with various ions, is prone to infiltrating both soil and groundwater, thereby engendering diverse PFOA-ion occurrence environments. However, the attenuation mechanism governing PFOA within the context of various PFOA-ion occurrence environments, specifically in conjunction with microbe−mineral interactions, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research findings have demonstrated that the release of SO 4 2– , NO 3 – , and HCO 3 – ions were a common occurrence in areas associated with chemical plants, agricultural activities, and mining operations. The coastal regions adjoining seawater environments typically featured the presence of Cl – –Na + ions . Given these circumstances, PFOA, in conjunction with various ions, is prone to infiltrating both soil and groundwater, thereby engendering diverse PFOA-ion occurrence environments.…”
Section: Introductionmentioning
confidence: 99%